2011
DOI: 10.1021/jm200450h
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Antimicrobial Peptidomimetic (LTX 109): Stereochemical Impact on Membrane Disruption

Abstract: LTX 109 is a synthetic antimicrobial peptidomimetic (SAMP) currently in clinical phase II trials for topical treatment of infections of multiresistant bacterial strains. All possible eight stereoisomers of the peptidomimetic have been synthesized and tested for antimicrobial effect, hemolysis, and hydrophobicity, revealing a strong and unusual dependence on the stereochemistry for a molecule proposed to act on a general membrane mechanism. The three-dimensional structures were assessed using nuclear magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
149
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(158 citation statements)
references
References 45 publications
7
149
0
2
Order By: Relevance
“…LTX-109 (Lytixar; Lytix Biopharma AS, Oslo, Norway) is one such novel SAMP which rapidly kills bacteria via membrane disruption and has not been associated with cross-resistance to other available drugs. LTX-109 has also been shown to have a low propensity for the development of resistance (5,6,8).…”
mentioning
confidence: 99%
“…LTX-109 (Lytixar; Lytix Biopharma AS, Oslo, Norway) is one such novel SAMP which rapidly kills bacteria via membrane disruption and has not been associated with cross-resistance to other available drugs. LTX-109 has also been shown to have a low propensity for the development of resistance (5,6,8).…”
mentioning
confidence: 99%
“…The mechanism of action of LTX-109 represents a new and innovative bactericidal approach via a direct membrane disruption (17,18). The product has been shown not to be affected by cross-resistance to other available drugs and has demonstrated a low propensity for development of resistance (17,18,24). In the present study, a significant reduction of S. aureus CFU was demonstrated already after 2 days, although bacterial recurrence was observed in all but one subject 5 days after the end of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…LTX-109 is a broad-spectrum, fast-acting bactericidal antimicrobial drug that binds to negatively charged membrane components on the bacterial cell, which is followed by membrane disruption and cell lysis (17,18). Nonclinical and clinical studies have demonstrated that topical application of LTX-109 (1 to 5%) has a good safety profile and a low bioavailability (19).…”
mentioning
confidence: 99%
“…When the Cterminus of this molecule was capped by an ethylphenylg roup,L TX-109w as obtained, which is undergoing clinical trials (Table 7, Structure 18). [47] Over severaly ears, Bremner et al attempted to mimic the action of vancomycin by designing small cationic cyclic peptoids.…”
Section: Structures That Use Amino Acids/peptidesmentioning
confidence: 99%
“…[47] From the data furnished on the company website, it is apparent that these short cationic peptidomimetics werea blet oa chieve antimicrobial activity against MRSA in am ouse skin infection model with efficacies better than the approved drugs Albataxa nd Fucidin. [3] In fact, they have recently shown the efficacy of LTX-109a sanovel agent for nasal decolonizationo fm ethicillin-resistant and -sensitive S. aureus in humans.…”
mentioning
confidence: 99%